Faktor Risiko Merokok Dengan Kejadian LupusDi Solo Raya - Fitriana Susanti, Eva; , Heru Subaris Kasjono SKM., M.Kes; , Anisa Catur Wijayanti, S.KM.,M.Epid (2016)
Lupus until now attacked at least about 5 million people in the world. Patients with lupus in Indonesia in 1998 recorded 586 cases, in 2005 as many as 6578 cases, in 2008 there were 8693 cases and in April 2009 there were 8,891 patients with lupus. This study aims to identify risk factors of smoking with the incidence of lupus in Solo Raya. This research is case-control study. The total of sample is 72 peoples. The bivariate analysis using Chi Square and Fisher's Exact Test. Multivariate analysis using logistic regression test. The results of bivariate analysis showed that there was no association between environmental exposure of tobacco in family (p = 0.234), there is anassociation between the environmental exposure oftobaccosmoke in the workplace (p = 0.009), there was no association between the exposure of tobacco smoke in (p = 0.056) there is anassociation between exposure oftobacco smoke in public transportation (p = 0.000) with the incidence of lupus in Solo Raya. While the results of multivariate analysis showed that exposure oftobacco smoke in public transportation has the highest risk 10.737 (95% CI = 2.159 to 53.390), it means that a person who expose to tobacco smoke in public transportation has amounted to 10.737 times risk for triggering lupus.